2015
DOI: 10.1001/jamadermatol.2015.0510
|View full text |Cite
|
Sign up to set email alerts
|

Nodular Amyloidosis of the Penis

Abstract: Lace bug infestations may have health consequences, including nuisance biting and cutaneous and systemic reactions. Clinicians should be aware of the existence of this insect with its newly recognized bloodsucking ability as potentially responsible for skin lesions and pruritus that can cause real discomfort and anxiety. Bites from the lace bug may also be considered in the differential diagnosis of bedbug bites 5 and scabies. 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…3 It has been reported that treatment with both H2A and LA in combination with sgH1AH is effective for many CIU patients. 4,5 This study suggests that treatment with both H2A and LA in combination with sgH1AH increases the therapeutic effect for CIU.…”
mentioning
confidence: 71%
“…3 It has been reported that treatment with both H2A and LA in combination with sgH1AH is effective for many CIU patients. 4,5 This study suggests that treatment with both H2A and LA in combination with sgH1AH increases the therapeutic effect for CIU.…”
mentioning
confidence: 71%
“…1 Less commonly, it can present as nodular amyloidosis where the amyloid protein is immunoglobulin-derived from plasma cells, serum amyloidassociated protein-derived, amyloid protein P-derived or in rare case reports, also keratinocyte-derived. [1][2][3][4] The involvement of the glans penis by primary cutaneous amyloidosis is a rare condition with less than 20 reported cases in literature to date. 2,3,5 These patients typically present with an asymptomatic, single, tan/yellow, waxy nodule, or plaque on the glans.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The involvement of the glans penis by primary cutaneous amyloidosis is a rare condition with less than 20 reported cases in literature to date. 2,3,5 These patients typically present with an asymptomatic, single, tan/yellow, waxy nodule, or plaque on the glans. Given the rarity and subtle findings of this condition, the diagnosis can be challenging clinically and histologically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The macular and lichenoid types integrate amyloid material from keratinocytes and deposit within the papillary dermis. 4 The nodular form can infiltrate the subcutis. 5 Nodular primary localized cutaneous amyloidosis (NPLCA) can appear as plaques or nodules that are waxy, yellow, and are more often on the face and leg.…”
mentioning
confidence: 99%